Konceptutveckling av konferensverksamheten vid Nordkalotten hotell och konferens med hjälp av omvärldsanalys och upplevelseproduktion : Sociala medier som upplevelserum till konferenser - Eriksson, Marina; Öman, Paola (2013)
The purpose of this paper is to study trends within the meeting industry of today to create a concept development through the use of business intelligence tool and theories from experience production. The developed concept has been applied to Nordkalotten Hotel and Conference. The paper has been prepared with a hermeneutic and inductive approach and a qualitative approach theory. The empirical material was generated through one interview and a business intelligence survey. The result of this paper is to recommend the use of social media as a relationship-building communications tool for companies and organizations in the conference industry. Validerat; 20131217 (global_studentproject_submitter)